Insulin and IGF-I inhibit GH synthesis and release in vitro and in vivo by separate mechanisms. - Gahete, MD; Córdoba-Chacón, J; Lin, Q; Brüning, J; Kahn, C; Castaño, J; Christian, H; Luque, R; Kineman, R (2013)
IGF-I is considered a primary inhibitor of GH secretion. Insulin may also play an important role in regulating GH levels because insulin, like IGF-I, can suppress GH synthesis and release in primary pituitary cell cultures and insulin is negatively correlated with GH levels in vivo. However, understanding the relative contribution insulin and IGF-I exert on controlling GH secretion has been hampered by the fact that circulating insulin and IGF-I are regulated in parallel and insulin (INSR) and IGF-I (IGFIR) receptors are structurally/functionally related and ubiquitously expressed. To evaluate the separate roles of insulin and IGF-I in directly regulating GH secretion, we used the Cre/loxP system to knock down the INSR and IGFIR in primary mouse pituitary cell cultures and found insulin-mediated suppression of GH is independent of the IGFIR. In addition, pharmacological blockade of intracellular signals in both mouse and baboon cultures revealed insulin requires different pathways from IGF-I to exert a maximal inhibitory effect on GH expression/release. In vivo, somatotrope-specific knockout of INSR (SIRKO) or IGFIR (SIGFRKO) increased GH levels. However, comparison of the pattern of GH release, GH expression, somatotrope morphometry, and pituitary explant sensitivity to acute GHRH challenge in lean SIRKO and SIGFRKO mice strongly suggests the primary role of insulin in vivo is to suppress GH release, whereas IGF-I serves to regulate GH synthesis. Finally, SIRKO and/or SIGFRKO could not prevent high-fat, diet-induced suppression of pituitary GH expression, indicating other factors/tissues are involved in the decline of GH observed with weight gain.